2016
DOI: 10.1093/ofid/ofw099
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Is Poorly Associated With Drug Use in Cambodian Americans in Lowell, Massachusetts

Abstract: Background. Hepatitis C (HCV) is the most common chronic blood-borne infection in the United States and affects Asian and non-Asian Americans comparably. Injection drug use, the most common national transmission risk, is not as prevalent in Asian-Americans, but prior studies do not include many Cambodian Americans. Lowell, Massachusetts has the second largest population of Cambodian Americans, allowing a direct comparison of HCV-infected Cambodian and non-Cambodian Americans not previously done. Improving our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For men, only having a tattoo or scarifications and living with a household member with liver disease were independently associated. Though other studies in Cambodia or among Cambodian natives have already identified iatrogenic exposure as a risk factor, none have suggested a gender difference [ 19 , 20 , 36 ]. Our finding is coherent with the previously documented higher usage of injections/infusions among women (7.5 vs. 4.3 per person-year in men) [ 18 ] and the higher likelihood of exposure to potentially unsafe invasive medical procedures because of female healthcare needs (prenatal vaccination, abortion, delivery, anticonception).…”
Section: Discussionmentioning
confidence: 99%
“…For men, only having a tattoo or scarifications and living with a household member with liver disease were independently associated. Though other studies in Cambodia or among Cambodian natives have already identified iatrogenic exposure as a risk factor, none have suggested a gender difference [ 19 , 20 , 36 ]. Our finding is coherent with the previously documented higher usage of injections/infusions among women (7.5 vs. 4.3 per person-year in men) [ 18 ] and the higher likelihood of exposure to potentially unsafe invasive medical procedures because of female healthcare needs (prenatal vaccination, abortion, delivery, anticonception).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, less common risk factors including dental care, surgeries outside of the United States, acupuncture, tattoos, and body piercing have been associated with HCV infection in Asian Americans [ 19–21 ]. In some studies, HCV-infected Asian Americans had no identifiable risk factors, making universal HCV screening all the more critical [ 12 , 19 , 22 , 23 ]. Thus, effective and culturally appropriate strategies to enhance HCV screening among Asian Americans remain timely and critical.…”
mentioning
confidence: 99%